Strong measurement method of evidence conflict based on earth mover’s distance - Xin WANG; Wei FU (Tongxin xuebao)
Aiming at the problem that the conflict factor k in D-S evidence theory cannot effectively measure the degree of conflict between two bodies of evidence (BoEs), the expected features of evidence conflict strong measurement function (ECSMF) were proposed, and then a new method of evidence conflict measurement based on earth mover’s distance (EMD)was put forward.The same number of focal elements between different BoEs was not required and the evidence conflict with non-singleton propositions could be directly calculate.The proposed method did not require The theory and experiments show that the size of conflict measure proposed can correctly represent the degree of conflict between two BoEs, and has all the expected features of ECSMF, which is an effective method of evidence conflict strong measurement.